Proceedings of the 41st Annual Meeting on Association for Computational Linguistics - ACL '03 2003
DOI: 10.3115/1075096.1075158
|View full text |Cite
|
Sign up to set email alerts
|

Learning to predict pitch accents and prosodic boundaries in Dutch

Abstract: We train a decision tree inducer (CART) and a memory-based classifier (MBL) on predicting prosodic pitch accents and breaks in Dutch text, on the basis of shallow, easy-to-compute features. We train the algorithms on both tasks individually and on the two tasks simultaneously. The parameters of both algorithms and the selection of features are optimized per task with iterative deepening, an efficient wrapper procedure that uses progressive sampling of training data. Results show a consistent significant advant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…These studies are firstly situated in the domain of psycholinguistics, where several experiments demonstrate that the familiarity or frequency of prosodic parameters influence speech processing, perception and production (Braun et al, 2006;Braun and Johnson, 2011;Mandel et al, 1994;. A second research area which provides evidence for lexicalised storage of intonation is the area of machine learning, where various studies showed that word identity helps in predicting pitch accent location (Brenier et al, 2006;Nenkova et al, 2007;Pan and Hirschberg, 2000;Pan and McKeown, 1999), and where instance-based learning of prosody outperforms other types of learning (Marsi et al, 2003).…”
Section: Lexicalised Storage Of Intonationmentioning
confidence: 98%
“…These studies are firstly situated in the domain of psycholinguistics, where several experiments demonstrate that the familiarity or frequency of prosodic parameters influence speech processing, perception and production (Braun et al, 2006;Braun and Johnson, 2011;Mandel et al, 1994;. A second research area which provides evidence for lexicalised storage of intonation is the area of machine learning, where various studies showed that word identity helps in predicting pitch accent location (Brenier et al, 2006;Nenkova et al, 2007;Pan and Hirschberg, 2000;Pan and McKeown, 1999), and where instance-based learning of prosody outperforms other types of learning (Marsi et al, 2003).…”
Section: Lexicalised Storage Of Intonationmentioning
confidence: 98%
“…Up to now, virtually no exemplar-theoretic research has examined pitch accent prosody (but see Marsi et al (2003) for memory-based prediction of pitch accents and prosodic boundaries, and Walsh et al (2008)(discussed below)) and to the authors' knowledge this paper represents the first attempt to examine the relationship between pitch accent prosody and information status from an exemplar-theoretic perspective. Given the considerable weight of evidence for the influence of frequency of occurrence effects in a variety of other linguistic domains it seems reasonable to explore such effects on pitch accent and information sta-tus realisations.…”
Section: Exemplar Theorymentioning
confidence: 97%
“…Several prosodic annotation systems have been previously proposed. Some of them combine acoustic, lexical and syntactic features (e.g., [5] for American English, [6] for French), others use lexical and syntactic information alone (e.g., [7] for Dutch). Since our aim is to build a tool that can be incorporated into the annotation process of a not-yet annotated database and also into an automatic speech recognition (ASR) system, the requirement for the system is to exclusively use acoustic information.…”
Section: Prosodic Boundary Detection Toolsmentioning
confidence: 99%